Avaliação da aprendizagem em jogos digitais baseada em learning analytics sobre dados multimodais - Pereira Junior, Heraclito Amancio (2018)
The use of digital games as a pedagogical tool has been successfully applied in the development of the skills, abilities and attitudes required of 21st century professionals, both in primary and secondary education, as well as in vocational training. Despite this, one issue has worried educators who think of using digital games: "How to assess the learning of digital games?". Assessment is an important part of the teaching-learning process. This importance, especially with regard to learning based on computational resources, including digital games, led to the emergence of a research area called Learning Analytics, which "applies techniques and methods of Computer Science, Pedagogy, Sociology, Psychology, Neuroscience and Statistics for the analysis of data collected during educational processes". In order to better understand these assessments, the collection has also considered multimodal data, those from different manifestations of the student, captured by sensors, during the learning process (touches, gestures, voices and facial expressions). Although the publications indicate that some methods, techniques and tools have been researched to support learning assessments in learning computing environments, and these studies have already obtained some results, they have not yet been sufficient to provide clear, comprehensive. In particular, with regard to digital games, there is still limited availability of consolidated resources for assessing student learning during play, which has been one of the major factors hindering a broadening of its use for educational purposes. This work brings a contribution to the solution of this problem through: a computational platform, in the form of a framework, designed based on the techniques and methods of Learning Analytics; a specialization of the ECD (Evidency Center Design) approach, for project evaluations of learning based on digital games, and a Process that organizes the stages and activities of this type of evaluation. Experiments, reported here, using a framework instance, have demonstrated both their own merit as an assessment tool and the specialization of ECD and the said process.